Evaluating the implementation and use of patient-reported outcome measures in a mental health hospital in Denmark: a qualitative study. (31st March 2022) - Kristensen, Solvejg; Holmskov, Jens; Baandrup, Lone; Videbech, Poul; Bonde, Maria; Mainz, Jan
Abstract: Background: Reporting of barriers and successes associated with the implementation and use of patient-reported outcomes (PROs) is limited as a means to ensure enhanced patient involvement, shared decision-making and improved treatment and care. We set out to evaluate the implementation and use of the PRO-Psychiatry initiative on patient-reported outcome measures in Danish mental health care. We aimed to described four specific areas: the quality of the clinical consultations before and after the implementation of PRO-Psychiatry as perceived by the patients (objective A), the motivation for participating in PRO-Psychiatry as perceived by patients and clinicians (objective B), the implementation process as perceived by patients, clinicians and managers (objective C) and suggestions for improvement (objective D). Methods: The PRO-Psychiatry initiative was evaluated through a participatory approach, including patients, clinicians and managers. A repeated cross-sectional interview-based survey explored the quality of the clinical consultation before and after the implementation of PRO-Psychiatry. A three-step semi-structured group interview, inspired by the modified mini-Delphi method, was used to establish consensus on the evaluation of the implementation and use of the initiative. Results: The evaluation pointed at PRO-Psychiatry as a meaningful initiative, which motivated patients and supported clinicians. The patients emphasised the importance of PROs, but they also found that PROs were not used enough. Clinically relevant improvements were detected after the implementation of the initiative; more patients felt heard and experienced that clinicians took a greater interest in their problems. The clinicians valued the easily accessible real-time graphical display of the PRO responses in the electronic health record (EHR). Clinicians and managers agreed that clinical PRO practices, patient compliance and use of PROs in treatment and care should be supported during implementation. Conclusion: The evaluation was overall positive. Patients and clinicians were willing to participate, found the online reporting easy and valued the direct access to PRO responses in the EHR. An essential feature was the integration of well-defined and functional PRO practices into the existing clinical workflow. Using PROs in the clinical sessions in a way that was palpable to the patient was found to be a significant improvement need. At the individual level, PRO-Psychiatry can use patient outcome information to support dialogue, encourage shared decision-making and promote self-management during recovery. At the aggregated patient level, the PROs can be used for monitoring the patient-perceived quality of care and for research.